3D interconnected structure of poly(methyl methacrylate) microbeads coated with copper nanoparticles for highly thermal conductive epoxy composites. (15th October 2019) - Vu, Minh Canh; Bach, Quang-Vu; Nguyen, Dinh Duc; Tran, Tuan Sang; Goodarzi, Marjan
Abstract: Polymer based composites as thermal management materials have become one of the most critical components in the design of modern microelectronic devices. Strategies to improve the thermal conductivities of the polymer composites such as introducing thermally conductive fillers into polymer matrices have received increasing interests. However, enhancements in the thermal conductivities are still limited even at high loadings of fillers, which may be due to lack of efficient heat conduction pathways. This study presents a facile and scalable method to fabricate highly thermal conductive epoxy composites possessing continuous 3D interconnected networks, which allows excellentat thermally conductive pathways throughout the epoxy matrix. Copper nanoparticles were first coated on poly (methyl methacrylate) microbeads to form Cu@PMMA by electroless-plating to prepare thermally conductive filler. Thereafter, the filler was incorporated into an epoxy matrix at different concentrations. The thermal conductivities of the composites are improved with increasing the Cu@PMMA filler content. The composites with a filler concentration of 50 wt% achieves a thermal conductivity of 3.38 W m −1 K −1, which is over 14-folds compared to the neat epoxy. In addition, the curing temperature slightly affects the thermal conductivities at filler contents lower than 30 wt%; however, it significantly enhances the thermal conductivities at filler contents higher than 30 wt%. On the other hand, increasing the weight fraction of Cu@PMMA filler retards the volume resistivities of the composites. A reduction of 11 orders of magnitude is observed for the volume resistivity of the composite loaded with 50 wt% filler (1.9 × 10 4 Ω·cm) when compared to that of the pure epoxy (4.5 × 10 15 Ω·cm).